Levees for a hundred-year flood: impact of a syndrome-based antimicrobial stewardship intervention for coronavirus disease 2019 on antimicrobial use and resistance - Alfredo J. Mena Lora; Rodrigo Burgos; Dylan Huber; Lawrence Sanchez; Mirza Ali; Candice Krill; Eden Takhsh; Susan C. Bleasdale (Cambridge University Press, 2024)
Coronavirus disease 2019 can be indistinguishable from lower respiratory tract infections (LRTIs) caused by other viral and bacterial agents. This likely contributed to antimicrobial use (AU) and antimicrobial resistance (AMR) during the pandemic. Our antimicrobial stewardship program targeted the selection and duration of therapy for LRTIs and led to a reduction in AU and AMR.